Pure Brucellar Discitis Mimicking Lumbar Disc Herniation: A Case Report and Review of The Literature - (:unkn) unknown (My University, 2013)
Brusellozis, zoonotik bir enfeksiyon olup; Orta Doğu, Akdeniz bölgesi, Orta ve Güney Amerika'da endemiktir. Kemik-eklem tutulumu en yaygın hastalık formudur; omurga bu grubun içinde üçüncü sıradadır. Bu yazıda, lomber disk hernisi kliniği ile başvuran 36 yaşında erkek hastayı sunmaktayız. Lomber manyetik rezonans görüntülemede, sağ L5-S1 ekstrüde disk hernisi saptandı ve hasta opere edildi. Frozen tanısı enflamatuvar süreç olarak raporlandı ve doku kültüründe Brusella melitensis üredi. Rifampisin ve doksisiklin tedavisi aldı. Altı ay sonraki takibinde kliniği, laboratuvar ve radyoloji tetkik sonuçları normal geldi. Klinik takipleri devam etmekle beraber medikal tedavisi 6 ay sonunda sonlandırıldı. Spondilit olmadan diskit, brusella hastalığında oldukça nadirdir. Literatürde bugüne kadar bildirilen benzer 2 olgu daha mevcuttur. Endemik bölgelerde, lomber disk hernisi ayırıcı tanısında Brusella diskiti akılda tutulmalıdır.

Brucellosis is a zoonotic infection, endemic in the Middle East, the Mediterranean region, Central and South America. Osteoarticular involvement is the most common form of the disease process with spinal complications in third place in this group. We presented a 36-year- old male patient with signs and symptoms of lumbar disc herniation. On lumbar magnetic resonance imaging, a right-sided L5-S1 disc extrusion was detected and the patient was operated. Frozen material pointed out an inflammatory process with Brucella melitensis in disc specimen culture. He was put on rifampicin and doxycycline chemotherapies. After 6 months of follow-up; his clinical, laboratory, and radiological findings became normal. Medical treatment was stopped with ongoing routine outpatient follow-ups. Discitis without spondylitis in Brucella infection is very rare. There have been 2 case reports in the literature. Also, Brucella disc infection should be in differential diagnosis of lumbar disc herniation clinic in endemic parts of the world.
Lomber Disk Hernisini Taklit Eden Saf Brusellar Diskit: Bir Olgu Sunumu ve Literatürün Gözden Geçirilmesi
Keywords: Nörolojik Bilimler